2006
DOI: 10.1016/j.bbmt.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

National Institutes of Health Consensus Development Project on Criteria for Clinical Trials in Chronic Graft-versus-Host Disease: VI. Design of Clinical Trials Working Group Report

Abstract: The complexity of chronic graft-versus-host disease (GVHD) and the lack of established research methods have made it difficult to design, conduct, and analyze clinical trials involving subjects with this disease, even when promising treatment options are available. This consensus document was developed to offer an approach for overcoming these obstacles. Clinical trials in chronic GVHD should adhere to principles of good trial design and practice. Inclusion and exclusion criteria should allow as many subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 13 publications
2
123
0
2
Order By: Relevance
“…The diagnosis and grading of acute and chronic GvHD was assigned by the transplant center using standard criteria. 21,22 Statistical analysis Median values and ranges were used for continuous variables and percentages for categorical variables (Table 1). For each continuous variable, the study population was initially split into quartiles and in two groups by the median.…”
Section: Endpointsmentioning
confidence: 99%
“…The diagnosis and grading of acute and chronic GvHD was assigned by the transplant center using standard criteria. 21,22 Statistical analysis Median values and ranges were used for continuous variables and percentages for categorical variables (Table 1). For each continuous variable, the study population was initially split into quartiles and in two groups by the median.…”
Section: Endpointsmentioning
confidence: 99%
“…Desta maneira, um grupo de trabalho do National Institutes of Health (NIH) desenvolveu um projeto para consenso dos critérios que deverão ser utilizados em estudos clínicos da DECH-c, [8][9][10][11][12][13] padronizou as características utilizadas no diagnóstico e propôs meios para a pontuação dos órgãos envolvidos e avaliação global da gravidade. 8 Estes critérios são úteis para uma melhor análise da incidência da DECH-c, além de poder avaliar a gravidade do comprometimento de um órgão, ou local, isolado, ou combinado, e a influência na mortalidade tardia do transplante.…”
Section: Critérios Para O Diagnóstico E Classificação Da Doença Enxerunclassified
“…It is suggested that progression of cGVHD despite 1 mg/kg/day of corticosteroids for 2 weeks or lack of improvement in symptoms after 4-8 weeks of continuous therapy or inability to taper corticosteroids should be considered as refractory disease [121]. The endpoints for the treatment of cGVHD is subjective and some of the effects of cGVHD are irreversible.…”
Section: Second-line Treatment Of Cgvhdmentioning
confidence: 99%